«Բարեկամական հարաբերություններ» իմաստային դաշտն արտահայտող դարձվածային միավորներն անգլերենում, հայերենում և իսպաներենում - Զարուհի Սողոմոնյան (ՀՀ ԳԱԱ հրատ.)
С древних времен пословицы считаются сокровищницей национальной мудрости, человеческого опыта, общих образов и языковых отношений. В сопоставительных трех языках выявление пословиц и поговорок дает более обобщенное представление о сходствах и различиях гиперконцепта “семья” в английской, армянской и испанской лингвокультурах. Proverbs have always been considered as a treasury of national wisdom, human experience, universal images and linguistic relations. Revealing idiomatic units of the hyper–concept ‘’family’’ in three languages under study will allow drawing a holistic picture of similarities and differences of linguacultures to be compared.
Keywords: Philology; Linguistics; Language and Literature